Method for preparing artificial graphite from waste coke powder

Through the high-temperature graphitization and pre-oxidized asphalt mixed granulation process, the problems of low tap density and insufficient capacity of waste coke powder are solved, and high-performance porous carbon materials are formed, which significantly improves the energy density and cycle stability of lithium-ion batteries. Low-cost and high-capacity negative electrode material preparation is achieved.

CN119176553APending Publication Date: 2024-12-24SHIJIAZHUANG SHANGTAI TECH CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411325775.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

In the existing graphite production process, the low tap density and insufficient capacity of waste coke powder lead to poor energy density and cycle stability of the negative electrode of lithium-ion battery, and poor processing performance, which cannot meet the high energy density and high charge and discharge rate. need.

Method used

The waste coke powder is graphitized at high temperature, mixed with preoxidized asphalt and granulated and carbonized under oxygen-free conditions to form a carbon cladding layer with holes, improve the tap density and pore structure of graphite, and increase the transmission of lithium ions. Contact area.

Benefits of technology

Artificial graphite with high compaction density, high capacity and high rate performance has been achieved, which has significantly improved the cycle stability and electrochemical performance of lithium-ion batteries, reduced production costs, and improved raw material utilization and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176553A_ABST
    Figure CN119176553A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of artificial graphite production, and particularly discloses a method for preparing artificial graphite from waste coke powder. According to the preparation method of the artificial graphite provided by the invention, by-product micro powder generated in a raw material coke grinding stage is used as a raw material, an asphalt substance is used as a binder, the asphalt substance is subjected to aerobic baking, part of the asphalt substance is oxidized in the baking process, the asphalt substance and waste coke powder are mixed and granulated, and the artificial graphite is obtained. In the subsequent carbonization process, the oxidized substances can form special holes in the surface of the graphite, the special carbon coating layers with the holes enable the artificial graphite to have good porosity, and the problem that the tap density is low after the waste coke powder is granulated is solved. When the artificial graphite is applied to the lithium ion battery, the electrochemical performance of an electrochemical device comprising the negative electrode material is favorably improved. The invention provides a low-cost and high-performance negative electrode material for the lithium ion battery, and has very important significance for the development of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of artificial graphite production, and in particular to a method for preparing artificial graphite by utilizing waste coke powder. Background Art

[0002] The negative electrode is the main component of lithium-ion batteries, and the negative electrode material is a key factor in determining battery performance. Graphite has excellent electrical conductivity and electronic conductivity. At the same time, it can form a stable SEI film with lithium ions, so it is widely used in the negative electrode of lithium-ion batteries. At present, the market is in urgent need of batteries with higher energy density and higher charge and discharge rates, which requires the capacity of the graphite negative electrode to be higher, provide more transmission channels for lithium ions, and have a shorter transmission path. Therefore, it is very necessary to develop a new generation of high-capacity and high-rate graphite.

[0003] A large amount of micropowders are generated during the raw coke grinding stage of graphite production. These micropowders can provide more transmission channels for lithium ions in the actual production and application process due to their low particle size. However, the fluffy characteristics of these micropowders result in low energy density and poor processing performance. Therefore, in actual production, these micropowders are usually sold to other industries at a low price, and the value they generate for enterprises is low. The products obtained by simply granulating the micropowders or directly graphitizing them using traditional processes often have the following two problems: (1) low tap density, which makes it difficult to mix the slurry during subsequent processing; (2) low capacity and low compaction, which results in the energy density of the negative electrode sheet not meeting the requirements, and cracking occurs at low pressure during coating. Therefore, it is necessary to develop a new process for preparing artificial graphite from waste coke powder to improve the tap density and capacity of the product and provide new ideas for the production of artificial graphite negative electrode materials. Summary of the invention

[0004] In view of the problem that most of the existing waste coke powder is sold to other industries at a low price and has low value to enterprises, the present invention provides a method for preparing artificial graphite using waste coke powder. The present invention uses waste coke powder as raw material, graphitizes the waste coke powder at high temperature, mixes it with pre-oxidized asphalt, and granulates and carbonizes it under anaerobic conditions to obtain artificial graphite. The lithium ion battery prepared with the artificial graphite as the negative electrode material has the advantages of high compaction density, high initial efficiency and high capacity retention rate, and has broad application prospects in the field of lithium ion batteries.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] In a first aspect, the present invention provides a method for preparing artificial graphite using waste coke powder, comprising the following steps:

[0007] S1, collecting waste coke powder generated in the raw material coke grinding process, and graphitizing the waste coke powder to obtain graphitized fine powder;

[0008] S2, in an oxygen atmosphere, baking the asphalt binder at a high temperature to obtain a pre-oxidized asphalt binder;

[0009] S3, in an oxygen-free atmosphere, the graphitized micropowder is uniformly mixed with a pre-oxidized asphalt binder, granulated, and carbonized to obtain artificial graphite.

[0010] It should be noted that the waste coke powder mentioned in the present invention refers to the fine powder by-product produced in the grinding process of the raw coke for producing artificial graphite.

[0011] Compared with the prior art, the preparation method of artificial graphite provided by the present invention uses the by-product powder produced in the raw coke grinding stage as raw material, uses asphalt-like substances as binders, and aerobically bakes the asphalt-like substances. During the baking process, part of the asphalt-like substances are oxidized, and they are mixed with waste coke powder for granulation. In the subsequent carbonization process, these oxidized substances will form special holes on the graphite surface. These special porous carbon coatings make the artificial graphite have good porosity. Therefore, the pre-oxidized asphalt-like substances, on the one hand, play a role in adjusting the tap density and solve the problem of low tap density of waste coke powder after granulation. On the other hand, the pore structure of the artificial graphite is increased, so that the contact area between the artificial graphite and the electrolyte is increased, which effectively shortens the transmission path of lithium ions, thereby improving the rate performance and cycle stability of the lithium ion battery prepared from the artificial graphite.

[0012] The preparation method of artificial graphite provided by the present invention uses waste coke powder as raw material. The utilization value of this type of micropowder is relatively low. By reusing these micropowders, the utilization rate of the raw coke is improved, and a low-cost, high-capacity, high-rate performance artificial graphite negative electrode material is provided for lithium-ion batteries, achieving the purpose of reducing costs and increasing efficiency, having high economic and environmental benefits, and having high promotion and application value.

[0013] Furthermore, S1, the raw coke includes at least one of petroleum coke, needle coke or asphalt coke.

[0014] Furthermore, in S1, D50 of the waste coke powder is 2 μm to 6 μm.

[0015] Furthermore, in S1, the graphitization temperature is 2800° C. to 3000° C., and the graphitization time is 60 h to 80 h.

[0016] The preferred graphitization temperature can improve the electrochemical properties of the graphitized product and increase the specific capacity and first coulombic efficiency of the artificial graphite.

[0017] Furthermore, in S2, the aerobic environment is an air environment or an oxygen atmosphere.

[0018] Furthermore, in S2, the asphalt binder includes at least one of petroleum asphalt, coal asphalt or liquid asphalt.

[0019] Furthermore, in S2, the temperature of the high temperature baking is 200° C. to 300° C., and the time of the high temperature baking is 30 min to 60 min.

[0020] Aerobic baking of the binder can cause part of the binder to be oxidized. These oxidized binders will form pores on the surface of the artificial graphite during the subsequent carbonization process. These pore structures not only facilitate better penetration of the electrolyte into the electrode material, increase the contact area between the electrolyte and the electrode material, and thus improve the charging and discharging efficiency and rate of the battery; they can also serve as a buffer space to reduce the volume expansion and contraction caused by the insertion and extraction of lithium ions, thereby improving the mechanical stability and cycle life of the electrode material.

[0021] Furthermore, in S3, the mass ratio of the graphitized micropowder to the pre-oxidized asphalt binder is 100:1 to 100:15.

[0022] Mixing graphitized micropowder and pre-oxidized binder in the above proportion can not only make the prepared artificial graphite have a moderate tap density, solving the problem of low tap density of waste coke powder after granulation, which leads to difficulty in slurrying during subsequent processing, but also help to improve the volume energy density of the battery and ensure the cycle stability of the battery.

[0023] Furthermore, in S3, the oxygen-free environment is provided by an inert atmosphere. The inert gas may be nitrogen, argon, helium, etc. conventional in the art.

[0024] Furthermore, in S3, the mixing speed is 50 rpm to 500 rpm, and the mixing time is 5 min to 10 min.

[0025] Furthermore, in S3, the granulation temperature is 450°C to 650°C, the granulation rotation speed is 50rpm to 60rpm, and the granulation time is 60min to 240min.

[0026] Furthermore, in S3, the particle size of the granulation is 8 μm to 15 μm.

[0027] Furthermore, in S3, the carbonization temperature is 900° C. to 1200° C., and the carbonization time is 8 h to 15 h.

[0028] It should be noted that in S3, the particle size of the carbonized artificial graphite is 9 μm to 16 μm.

[0029] In a second aspect, the present invention further provides an artificial graphite prepared by any of the above-mentioned methods for preparing artificial graphite using waste coke powder.

[0030] In a third aspect, the present invention further provides a negative electrode, comprising the artificial graphite.

[0031] In a fourth aspect, the present invention also provides the use of the above-mentioned artificial graphite or the above-mentioned negative electrode in the preparation of a lithium-ion battery.

[0032] In a fifth aspect, the present invention further provides a lithium-ion battery, comprising the above-mentioned artificial graphite or the above-mentioned negative electrode.

[0033] In a sixth aspect, the present invention further provides a battery module, comprising the above-mentioned lithium-ion battery.

[0034] The present invention uses the byproduct micro powder generated in the raw material coke grinding stage as raw material, converts it into artificial graphite with a microporous structure through a specific process, and uses it as a lithium ion negative electrode material, which is beneficial to the embedding and rapid charging and discharging performance of lithium ions, and is also beneficial to improving the cycle stability performance of lithium ion batteries and improving the overall performance of lithium ion batteries. In addition, the cost of waste coke powder is relatively low. Using it as a raw material to prepare artificial graphite not only improves its production value, but also helps to reduce the production cost of lithium ion batteries. It has obvious economic and market advantages, and provides a new material with excellent comprehensive performance for lithium ion batteries, with broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM image of the artificial graphite prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0037] In order to better illustrate the present invention, further examples are given below.

[0038] Example 1

[0039] This embodiment provides a method for preparing artificial graphite, comprising the following steps:

[0040] Step a, collecting fine powder generated during the crushing process of needle coke using a grinding device, wherein the D50 of the fine powder is 2 μm to 6 μm;

[0041] Step b, charging the collected micro powder into an Acheson furnace for high temperature roasting, the roasting temperature is 2800° C., the roasting time is 70 hours, and graphitized micro powder is obtained;

[0042] Step c, baking the petroleum asphalt in air at 300° C. for 30 minutes to make it flowable, then mixing the graphitized micropowder with the flowable petroleum asphalt in a mass ratio of 100:5, and stirring and mixing at a rotation speed of 400 rpm for 5 minutes;

[0043] Step d, adding the mixed material into a granulation kettle, and then granulating at 550° C. and 50 rpm under a nitrogen atmosphere for 200 min to obtain secondary particles with a D50 of 8 μm to 15 μm;

[0044] Step e: carbonizing the secondary particles at 1050° C. for 10 h under a nitrogen atmosphere to obtain artificial graphite with a particle size of 9 μm to 16 μm.

[0045] The SEM image of the artificial graphite prepared in this embodiment is as follows: Figure 1 As shown in the figure, it can be seen that there are many porous structures on the surface of artificial graphite, which plays a very important role in improving the electrochemical properties of artificial graphite.

[0046] Example 2

[0047] This embodiment provides a method for preparing artificial graphite, comprising the following steps:

[0048] Step a, collecting micro powder generated during the crushing process of petroleum coke using a grinding device, wherein the D50 of the micro powder is 2 μm to 6 μm;

[0049] Step b, charging the collected micro powder into an Acheson furnace for high temperature roasting, the roasting temperature is 3000° C., the roasting time is 60 hours, and graphitized micro powder is obtained;

[0050] Step c, baking the coal tar pitch in air at 280° C. for 45 minutes to make it flowable, then mixing the graphitized micropowder with the flowable petroleum asphalt in a mass ratio of 100:1, and stirring and mixing at a rotation speed of 100 rpm for 8 minutes;

[0051] Step d, adding the mixed material into a granulation kettle, and then granulating at 650° C. and 60 rpm under a nitrogen atmosphere for 60 min to obtain secondary particles with a D50 of 8 μm to 15 μm;

[0052] Step e: carbonizing the secondary particles at 1200° C. for 8 h in a nitrogen atmosphere to obtain artificial graphite with a particle size of 9 μm to 16 μm.

[0053] Example 3

[0054] This embodiment provides a method for preparing artificial graphite, comprising the following steps:

[0055] Step a, collecting fine powder generated during the crushing process of the asphalt coke using a grinding device, wherein the D50 of the fine powder is 2 μm to 6 μm;

[0056] Step b, charging the collected micro powder into an Acheson furnace for high temperature roasting, the roasting temperature is 2900° C., the roasting time is 80 hours, and graphitized micro powder is obtained;

[0057] Step c, baking the liquid asphalt in air at 200° C. for 60 minutes, then mixing the graphitized powder with the baked liquid petroleum asphalt in a mass ratio of 100:15, and stirring the mixture at a rotation speed of 500 rpm for 10 minutes;

[0058] Step d, adding the mixed material into a granulation kettle, and then granulating at 450° C. and 55 rpm under a nitrogen atmosphere for 120 min to obtain secondary particles with a D50 of 8 μm to 15 μm;

[0059] Step e: carbonizing the secondary particles at 1200° C. for 8 h in a nitrogen atmosphere to obtain artificial graphite with a particle size of 9 μm to 16 μm.

[0060] Comparative Example 1

[0061] This comparative example provides a method for preparing artificial graphite. The only difference from Example 1 is that the high-temperature baking step of petroleum asphalt in step c is omitted. The specific steps are as follows:

[0062] Step a, collecting fine powder generated during the crushing process of needle coke using a grinding device, wherein the D50 of the fine powder is 2 μm to 6 μm;

[0063] Step b, charging the collected micro powder into an Acheson furnace for high temperature roasting, the roasting temperature is 2800° C., the roasting time is 70 hours, and graphitized micro powder is obtained;

[0064] Step c, crushing the petroleum asphalt to a particle size of 4 μm to 7 μm, then mixing the graphitized micropowder with the crushed petroleum asphalt in a mass ratio of 100:5, and stirring and mixing at a speed of 400 rpm for 5 minutes;

[0065] Step d, adding the mixed material into a granulation kettle, and then granulating at 550° C. and 50 rpm under a nitrogen atmosphere for 200 min to obtain secondary particles with a D50 of 8 μm to 15 μm;

[0066] Step e: carbonizing the secondary particles at 1050° C. for 10 h under a nitrogen atmosphere to obtain artificial graphite with a particle size of 9 μm to 16 μm.

[0067] Comparative Example 2

[0068] This comparative example provides a preparation process of a traditional artificial graphite, which specifically comprises the following steps:

[0069] Step a, collecting fine powder generated during the crushing process of needle coke using a grinding device, wherein the D50 of the fine powder is 2 μm to 6 μm;

[0070] Step b, crushing petroleum asphalt to a particle size of 4 μm to 7 μm, then mixing the collected micropowder with the crushed petroleum asphalt in a mass ratio of 100:5, and stirring and mixing at a speed of 400 rpm for 5 minutes;

[0071] Step c, adding the mixed material into a granulation kettle, and then granulating at 550° C. and 50 rpm under a nitrogen atmosphere for 200 min to obtain secondary particles with a D50 of 8 μm to 15 μm;

[0072] Step d, placing the secondary particles into an Acheson furnace for high-temperature calcination at a temperature of 2800° C. for 70 hours to obtain artificial graphite.

[0073] The artificial graphites prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested for particle size, specific surface area, and tap density, and the results are shown in Table 1. The particle size was measured using a particle size analyzer (Malvern Mastersizer 3000); the specific surface area was measured using a specific surface area measuring instrument (American Micromeritics Tristar 3030); and the tap density was measured using a tap density meter (BT-302).

[0074] Table 1

[0075]

[0076] Application Examples

[0077] The artificial graphites prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 2 were respectively assembled into batteries for electrochemical performance testing, and the specific steps were as follows:

[0078] (1) Preparation of negative electrode: N-methylpyrrolidone, polyvinylidene fluoride and conductive carbon black were mixed in a mass ratio of 94:3:3 to obtain a conductive glue; 15.9g of the conductive glue and 3.6g of the prepared artificial graphite were weighed and added to a stirring tank, and then placed in a degassing mixer. After stirring, the slurry fluidity was observed. If the slurry fluidity was normal, it could be coated. If the slurry fluidity was poor, an appropriate amount of N-methylpyrrolidone was added. During coating, the slurry was evenly coated on the surface of the copper foil with a scraper (30μm) to form a film, and then the electrode was placed in a 100℃ oven for drying for 2h, and then rolled and cut into 10mm diameter discs and weighed for standby use.

[0079] (2) Assembly of lithium-ion batteries: A metal lithium sheet with a diameter of 14 mm and a thickness of 1 mm was used as the counter electrode, a Celgard 2400 with a diameter of 24 mm and a thickness of 0.25 mm was used as the diaphragm, the 10 mm negative electrode sheet prepared above was used as the working electrode, and a solution of 1 mol / L LiPF6 dissolved in ethylene carbonate and ethyl methyl carbonate (volume ratio 3:7) was used as the electrolyte. The negative electrode shell, spring, gasket, metal lithium sheet, diaphragm, negative electrode sheet, and positive electrode shell were assembled from top to bottom in the glove box to obtain a button battery. Six batteries were assembled for each negative electrode material, and a total of six groups of data were tested. After removing the highest and lowest data, the average of the remaining four groups of data was taken as the battery performance data.

[0080] (3) The specific test conditions for the performance of the button cell are as follows: at room temperature of 25°C, using a blue battery tester, the assembled button cell is discharged at 0.05C to 5mV, then discharged at 0.05mA to 5mV, then discharged at 0.01mA to 5mV, and finally charged at 0.1C to 2.0V, and the discharge capacity and discharge efficiency during this process are recorded.

[0081] Rate test: At room temperature, 0.05C discharge to 5mV, stand for 10s, 0.1C charge to 2V, stand for 10s, 0.3C discharge to 5mV, stand for 10s, 0.3C charge to 2V, stand for 10s (3 cycles), 0.5C discharge to 5mV, stand for 10s, 0.5C charge to 2V, stand for 10s (3 cycles), 1C discharge to 5mV, stand for 10s, 1C charge to 2V, stand for 10s (3 cycles ), 2C discharge to 5mV, stand for 10s, 2C charge to 2V, stand for 10s (cycle 3 times), 3C discharge to 5mV, stand for 10s, 3C charge to 2V, stand for 10s (cycle 3 times), 4C discharge to 5mV, stand for 10s, 4C charge to 2V, stand for 10s (cycle 3 times), 5C discharge to 5mV, stand for 10s, 5C charge to 2V, stand for 10s (cycle 3 times), record 4C discharge capacity retention rate. The results are shown in Table 2.

[0082] Table 2

[0083]

[0084] The results show that the artificial graphite prepared in the embodiment of the present invention has a higher tap density than the comparative example, ensuring the processing performance. Comparative Examples 1 and 2 have difficulty in slurrying in the subsequent slurrying process. And through electrochemical testing, it is proved that the artificial graphite prepared in the embodiment of the present invention as a negative electrode material can significantly improve the electrochemical performance and cycle life of lithium-ion batteries, can meet the requirements of high energy density batteries, and can withstand higher pressures during coating without cracking (the comparative example has cracking problems during coating). The present invention provides a low-cost, high-performance negative electrode material for lithium-ion batteries, which is of great significance to the development of lithium-ion batteries.

[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing artificial graphite using waste coke powder, characterized in that: The steps include: S1, collecting waste coke powder generated in the raw material coke grinding process, and graphitizing the waste coke powder to obtain graphitized fine powder; S2, in an oxygen atmosphere, baking the asphalt binder at a high temperature to obtain a pre-oxidized asphalt binder; S3, in an oxygen-free atmosphere, the graphitized micropowder is uniformly mixed with a pre-oxidized asphalt binder, granulated, and carbonized to obtain artificial graphite.

2. The method for preparing artificial graphite using waste coke powder as claimed in claim 1, characterized in that: In S1, the raw coke includes at least one of petroleum coke, needle coke or pitch coke; and / or In S1, the D50 of the waste coke powder is 2 μm to 6 μm.

3. The method for preparing artificial graphite using waste coke powder as claimed in claim 1, characterized in that: In S1, the graphitization temperature is 2800° C. to 3000° C., and the graphitization time is 60 h to 80 h.

4. The method for preparing artificial graphite using waste coke powder as claimed in claim 1, characterized in that: In S2, the asphalt binder includes at least one of petroleum asphalt, coal asphalt or liquid asphalt; and / or In S2, the temperature of the high temperature baking is 200°C to 300°C, and the time of the high temperature baking is 30min to 60min.

5. The method for preparing artificial graphite using waste coke powder as claimed in claim 1, characterized in that: In S3, the mass ratio of the graphitized powder to the pre-oxidized asphalt binder is 100:1 to 100:15; and / or In S3, the granulation temperature is 450°C to 650°C, the granulation speed is 50rpm to 60rpm, and the granulation time is 60min to 240min; and / or In S3, the particle size of the granulation is 8 μm to 15 μm; and / or In S3, the carbonization temperature is 900° C. to 1200° C., and the carbonization time is 8 h to 15 h.

6. An artificial graphite, characterized in that: The artificial graphite is prepared by the method for preparing artificial graphite using waste coke powder as described in any one of claims 1 to 5.

7. A negative electrode, characterized in that Comprising the artificial graphite as described in claim 6.

8. Use of the artificial graphite according to claim 6 or the negative electrode according to claim 7 in preparing a lithium ion battery.

9. A lithium ion battery, characterized in that: It includes the artificial graphite as claimed in claim 6 or the negative electrode as claimed in claim 7.

10. A battery module, characterized in that: Includes the lithium ion battery as claimed in claim 9.

Citation Information

Cited By

  • Waste coke regenerated graphite, preparation method and application thereof, and lithium ion battery

    CN121717360A

  • Waste coke regenerated graphite, preparation method and application thereof, and lithium ion battery

    CN121717360B

  • Composite material and preparation method thereof, electrode and battery

    CN122417848A